Feasibility of robotic radical hysterectomy after neoadjuvant chemotherapy in women with locally advanced cervical cancer. Issue 9 (September 2016) - Minig, L.; Zanagnolo, V.; Cárdenas-Rebollo, J.M.; Colombo, N.; Maggioni, A.
Abstract: Objective: To evaluate the safety and feasibility of robotic radical hysterectomy (RRH) in women with locally advanced cervical cancer (LACC) after neoadjuvant chemotherapy (NACT). Material and methods: A retrospective comparative longitudinal observational study was performed in 30 patients with LACC FIGO stage IB2-IIB who underwent RRH after NACT between February 2008 and September 2014. This group was compared with a cohort of 176 patients underwent RRH with cervical cancer FIGO stage IA2-IB1 in the same period of time. Results: Patients' age, BMI, ASA score, comorbidity, and previous abdominal surgery, was similar between groups. FIGO stage significantly differed between groups; 29 (96.6%) of patients had FIGO stage IB2 in NACT group and 163 (92.6%) were FIGO stag IB1 in women without NACT, p  < 0.001. Type of RRH was also significantly different between groups. Type C1 RRH was significantly more common in NACT group, p  = 0.015. Mean (SD) tumor size was significantly bigger in NACT, 27.0 (13.7) mm versus 20.9 (9.0) mm in early stage versus LACC, respectively. p  = 0.023. Mean (SD) surgical time was significantly longer in NACT group (307.8 (40.2) min versus 277.4 (45.4) min, p  = 0.001). Estimated blood loss and length of the hospital stay were similar between groups. There were no significant differences in terms of intraoperative and postoperative complications. Conclusions: RRH after NACT in women with LACC seems to be safe and feasible. These results need to be confirmed in studies with a larger patients sample.